MICROSCOPY TECHNIQUES FOR INVESTIGATING NUTRITIONAL PROPERTIES OF CEREALS AND THEIR TRANSFORMATION INTO FOODSTUFFS (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
This review focuses on the combination of optical microscopy (OM) and Environmental Scanning Electron Microscopy-Energy Dispersive Spectroscopy (ESEM-EDS) in the anatomical and functional characterization of the cereal caryopsis in order to drive the technology of transformation as well as to save the nutrients in the flours and their derived products. With OM, we analyzed caryopsis sections stained with Azan Trichrome, Periodic Acid Shiff (PAS) and Toluidine blue staining. These techniques allowed the characterization of the aleuronic layers with their protein globoids and starch granules of variable dimensions in the endosperm. Fluorescence OM allowed to evidence phenolic compounds and soluble fibers, in particolar the Î²-glucan of oat and barley, with the aid of the dye Calcoflour white. ESEM-EDS does not require fixation or embedding of the samples, and the structures are visualized under natural conditions. By means of ESEM-EDS, we localized protein globoids, the germ with the depleted layer (which connects the germ to the endosperm) and the starch granules with their qualitative elemental composition. Referring to nutrition, microscopic analysis highlights the higher bioaccessibility of einkorn wheat starch granules during digestion. At the technological level, barley and oat are more suitable than einkorn for pearling and malting, due to their thicker and more robust cell walls.